Life Prediction and Stress Intensity Factor (SIF) analysis for the base straight component and weld straight component (Pipes) used in the nuclear power plant. (2017) - Dhakad, Shrikrishna; Saxena, Sanjeev; Purohit, Rajesh; Pandey, Utkarsh
Abstract: The present investigation, the fatigue crack growth behaviour of surface cracked piping, pressurized base straightcomponent(PBSC) andpressurized base straight weld component(PBWC)are performed on the basis of the linear elastic fracture mechanics (LEFM) principles. The stress intensity factors available in the open literature are evaluated to predict the crack growth behaviour of the component using the specimen tested material data. It is concluded that the available open literature stress intensity factor (SIF) solution like ASM and Bergman for external surface cracked straight pipe case having the semi-elliptical crack profile predicts the fatigue life of the component when having constant crack depth profile.